DIFFERENTIATED LEARNING STRATEGIES FOR ENHANCING ENGAGEMENT AND ACHIEVEMENT IN MATHEMATICS: A CLASSROOM ACTION RESEARCH STUDY - Siswanto, Deny Hadi; Syah, Arga Bagus Pratama Dyah Aan Firman; Kuswantara, Hary (CV. Denasya Smart Publisher, 2025)
This study aims to enhance students' engagement and mathematics achievement through the implementation of differentiated learning. The method employed is classroom action research conducted in two cycles, each consisting of planning, action implementation, observation, evaluation, and reflection stages. The research was carried out during the odd semester at SMK Muhammadiyah 1 Sleman with the participation of 28 students from the XI Automotive class. The findings reveal a significant improvement in students' engagement and learning outcomes. In the first cycle, the average engagement score was 9.51, which increased to 17.12 in the second cycle. Regarding learning outcomes, in the first cycle, only 10 students (35,71%) achieved the passing grade, while 18 students (64.29%) did not, with an average score of 64.75. In the second cycle, the number of students achieving the passing grade sharply increased to 28 students (100%) with an average score of 84.92. These results demonstrate that differentiated learning effectively enhances student engagement and mathematics achievement in the XI Automotive class at SMK Muhammadiyah 1 Sleman during the 2024/2025 academic year